UAV-based surveying in volcano-tectonics: An example from the Iceland rift. (April 2019) - Bonali, F.L.; Tibaldi, A.; Marchese, F.; Fallati, L.; Russo, E.; Corselli, C.; Savini, A.
Abstract: In the present work, we applied the use of an Unmanned Aerial Vehicle (UAV) - a quadcopter - and the Aerial Structure from Motion digital photogrammetry image processing technique (ASfM) to study volcano-tectonics and tectonic features in an active Icelandic rift. Data have been collected in order to evaluate the Holocene deformation in the Northern Volcanic Zone of Iceland. We mapped 397 structures, mainly related to extension fractures and subordinately normal faults in the Theistareykir Fissure Swarm, obtaining 1098 and 21 structural data, respectively. This allowed to reconstruct an overall spreading direction of N108° during Holocene times, and to calculate a stretch of 1.013 regarding 8–10 ka old lava units. Deformation in the area is related to both dyke intrusions and extensional tectonics. Furthermore, detailed geological-structural field and UAV surveys were also performed in two test areas in order to determine data accuracy and the associated reliability of this approach. In addition to the above, different flight heights were tested, suggesting that photo collection with a 12.4 MPx camera at 100 m is efficient to study fracture dilation and kinematics. Highlights: We studied Holocene deformations in Iceland's Northern Volcanic Zone. Extension fractures were studied by UAV and field surveys. We defined the geometry of 397 fractures and collected about 1119 structural data. The overall spreading direction of the area was N108° during the Holocene. We suggest an appropriate flight height for surveying extension fractures.